Pengaruh Kesadaran, Gaya Hidup, Dan Sertifikasi Halal Pada Minat Beli Produk Makanan Halal UMKM Di DKI Jakarta - Muhammad Rizky Taufiq Nur, (2021)
This research aims to explain the effect of awareness, lifestyle, and halal certification on people's buying interest in MSME halal food products in DKI Jakarta Province. Quantitative methods are used as research methods that refer to numerical data. The subjects in this research are 150 consumers of MSME halal food products in the DKI Jakarta Province. The research object is MSME halal food products. Primary data collection is used as a technical data collection. Primary data was taken through the distribution of questionnaires to MSME halal food consumers. Meanwhile, the data analysis technique used is descriptive statistical analysis, data quaity, classical assumptions, multiple linear regression, and hypotheses. The result obtained within this research are halal awareness has a significant influence on the purchase intention of MSME halal food products, halal lifestyle has a significant influence on the purchase intention of MSME halal food products, halal certification does not have a significant effect on buying interest MSME halal food products, as well as halal awareness, halal lifestyle and halal certification together have a significant influence on buying interest in MSME products. The contribution of this research is to provide an overview of the understanding of the awareness and lifestyle of the Muslim community in DKI Jakarta regarding the halal aspect and their views on halal certification.